THE INFLUENCE OF SHARE OWNERSHIP STRUCTURE AND INVESTMENT OPPORTUNITY SET ON FIRM VALUE - Listiana, Ayu Octavia (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
Examining how different types of ownership and investment options affect company value is the driving force behind this study. The mining businesses listed on IDX from 2019 to 2022 are the focus of this investigation. In this study, researchers used a purposive sampling strategy, which involved selecting participants according to predetermined criteria. There were 76 study samples that were chosen. This study qualifies as quantitative research due to the nature of the data used. Secondary data is used as the basis for this study. Methods such as documentation and literature review were used to gather data. Eviews, a statistical tool, is used to do panel data regression analysis on the collected data. Statistical methods such as partial hypothesis tests (t), coefficients of determination (R2), and simultaneous hypothesis tests (f) are used to analyze the data. The study's findings demonstrate that both the independent and dependent factors significantly impact one another. The determination test yielded an adjusted R2 value of 0.739091, which is equivalent to 73.91% (rounded). The remaining 26.09% were affected by factors that were not taken into account in this research. The subtest findings indicate that the factors of public ownership, investment possibilities, foreign ownership, and management ownership significantly affect the value of the organization.